Pola Asuh Keluarga Broken Home Terhadap Perilaku Belajar Siswa Di SMP Nurul Hasanah - Sagala, Gabe Erdiana; Ismail, Ismail (JURNAL MANAJEMEN PENDIDIKAN, 2025)
BROKEN HOME FAMILY PARENTING STYLE ON STUDENT LEARNING BEHAVIOR AT NURUL HASANAH JUNIOR HIGH SCHOOLThis study aims to describe the influence of parenting patterns in broken home families on the learning behavior of students at SMP Nurul Hasanah. This research used a qualitative method, with data collected through interviews with 10 students from broken home families (primary informants) and 5 parents (supporting informants). The findings show that changes in family structure following parental separation significantly affect students' learning behavior. Most students experienced decreased motivation, learning discipline, and enthusiasm due to unstable parenting patterns. In several cases, students became unfocused, socially withdrawn, and lost academic direction. Both permissive and authoritarian parenting styles tend to negatively impact the learning process. However, a democratic parenting style that emphasizes open communication, empathy, and emotional support was proven to help students maintain a consistent study routine. The study concludes that parenting patterns in broken home families can either hinder or support students’ learning behavior depending on the quality of interaction and emotional involvement provided. Therefore, active parental engagement and attention from the school are crucial in guiding students to develop optimally despite experiencing non-ideal family conditions.